In situ reverse transcription: the magic of strength and anonymity - Ligasová, Anna; Koberna, Karel (Nucleic acids research, 2010)
In this study, we describe an approach that enables a highly specific, effective and fast detection of polyadenylated RNA sequences in situ at the light and electron microscopy levels. The method developed is based on the incorporation of 5-bromo-2'-deoxyuridine into the growing cDNA strand by means of the reverse transcriptase. We have shown that unlike the previously used deoxyuridine tagged with biotin or digoxigenin, 5-bromo-2'-deoxyuridine is 'invisible' in the DNA-DNA duplex but easily detectable in the DNA-RNA duplex. This feature is an important pre-requisite for the correct interpretation of the data obtained, as our results strongly indicate that reverse transcriptase uses DNA breaks as primers efficiently. We have also shown that the replacement of deoxythymidine by 5-bromo-2'-deoxyuridine considerably stabilizes the growing DNA-RNA duplex, thus enabling the one-step detection of polyadenylated RNA in structurally well-preserved cells. The method developed provides a highly specific signal with the signal/noise ratio higher than 130 for permeabilized cells and 25 for conventional acrylic resin sections under the conditions used. When the high pressure freezing technique followed by the freeze substitution is employed for the cell's preparation, the ratio is higher than 80.
Keywords: Microscopy, Fluorescence; Tissue Embedding; akrylové pryskyřice; Humans; HeLa buňky; messenger RNA; zalévání tkání; In Situ Hybridization, Fluorescence; fluorescenční mikroskopie; permeabilita buněčné membrány; Reverse Transcription; lidé; reverzní transkripce; Acrylic Resins; RNA, Messenger; poly A; hybridizace in situ fluorescenční; HeLa Cells; Cell Membrane Permeability; Poly A